Engineering Education for Knowledge Society - Shetty, N. R.; Hariharan, R. (Journal of Engineering Education Transformations, 2006)
Engineering educators today must teach academic disciplines which encompass a greater range and depth of technology than ever before. Engineering graduates, on the other hand, are expected to combine detailed understanding of a subspecialty with the flexibility to adapt to new technologies, interdisciplinary challenges and a changing markup lace. A solution to this apparent dilemma can be found by considering a new paradigm for engineering education, which places specific engineering disciplines within the context of information technology. This paper outlines the current scenario and reviews the possible solutions.